The Activity Of Cellulose Enzyme From Indigenous Bacteria "Bacillus Sp YLB1" As Bioactivator - Yunilas; Lili Warly; Yetti Marli; Irsan Riyanto (Jurnal Peternakan Integratif, 2019)
This study aims to test the activity of cellulase enzyme (CMCase) fromindigenous bacteria "Bacillus Sp YLB1" as bioactivator of palm oil based feed. Thetreatment consists of various combinations of substart, namely: P1 = 80% palm leaves +10% palm kernel cake + 10% sludge; P2 = 60% palm leaves + 20% palm kernel cake +20% sludge and P3 = 60% palm leaves + 30% palm kernel cake+ 30% sludge. The parameters observed were cellulase enzyme activity (CMCase) onvarious combinations of palm oil waste and fermentation time. The results showed thatcellulase enzyme (CMCase) production of Bacillus sp YLB1 bacteria during fermentationfluctuated ie 0.143 Units / ml; 0.372 Units / ml; 0.588 Units / ml; 1.013 Units / ml; 0.906Units / ml; 1,065 Units / ml and 1,198 Units / ml.The activity of cellulase enzyme(CMCase) on substrate P1 is lower than P2 and P3. As conclutions that cellulase enzymeactivity of Bacillus sp YLB1 influenced by the combination of substrate and fermentationtime. The P3 fermented with Bacillus sp YLB1 for 7 days gave a more optimal result thanthe other treatments